HYPOTHYROIDISM - Mamaraximov Nursulton Alisherovich; Fayziyeva Dilshoda Ozod qizi; Normuradov Alisher Ismailovich (TADQIQOTLAR, 2026)
Annotation: hypothyroidism ( called low thyroid, low thyroid, or hypothyroidism) is a disorder of the endocrine system that produces thyroid hormone.nnotation: hypothyroidism ( called low thyroid, low thyroid, or hypothyroidism) is a disorder of the endocrine system that produces thyroid hormone. In this, it can cause snnotation: hypothyroidism ( called low thyroid, low thyroid, or hypothyroidism) is a disorder of the endocrine system that produces thyroid hormone. In this, it can cause symptoms such as a feeling of tiredness , decreased workload, depression. From time to time, the front of the neck can become larger due to the bulge. Untreated cases of hypothyroidism during pregnancy can lead to delayed growth and intellectual development in infant or congenital Iodine Deficiency Syndrome. Worldwide, too little iodine intake in the diet is the most common cause of hypothyroidism.orldwide, too little iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimoto is the cause of the most orldwide, too little iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimorldwide, too little iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimoto is theittle iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimoto is the cause of the most common occurrence of hypothyroidism in countries where insufficient iodine is not required. Less common causes include treatment with radioactive iodine, an injury to the anterior compartment of the hypothalamus or pituitary gland. The diagnosis of hypothyroidism, when suspected, can be confirmed by blood tests that measure Thyroid-Stimulating Hormone (TSH) and thyroxine levels. Salt iodization prevented hypothyroidism in most populations. Thyroid hormone replacement with levothyroxine treats hypothyroidism. Medical specialists need to adjust the dosage according to the symptoms and normalization of the levels of thyroxine and Thg.